On runway foreign object ingestion with a variable pitch fan in reverse thrust mode - Vitlaris, Dimitrios; Rajendran, David John; Tunstall, Richard; Moore, Barry; Clarkson, Rory; Pachidis, Vassilios (American Society of Mechanical Engineers (ASME), 2026)
The characterization and quantification of runway foreign object ingestion (FOI) at the end of the landing run with a variable pitch fan (VPF) in reverse thrust mode are described in this work. This is achieved by developing a novel, fully coupled computational fluid dynamics—discrete phase model (CFD-DPM) methodology that allows the tracking of individual debris, which is placed on the runway. The flow field solutions are computed by the three-dimensional (3D) Reynolds-averaged Navier–Stokes (RANS) equations, and the particulate phase is tracked in a Lagrangian way. A modern 300-seater aircraft is considered to feature a high bypass ratio geared turbofan engine architecture on a conventional twin-engine airframe in landing configuration that rolls on the runway at low speeds and a typical high engine power mode. The aerodynamic reverse thrust flow field at such low aircraft speeds is characterized by the development of a “horseshoe” vortex formed in front of the engine that significantly affects the debris trajectories. Based on this, two FOI mechanisms are identified and discussed in detail in the paper. The effect of key debris properties on FOI percentage, such as size, material density, and shape, are investigated and reported. Nonlinear, nonintuitive trends are obtained due to the two-way interaction of flow features and particles. Moreover, a nondimensional analysis that accounts for the changes in debris variables of interest is presented and provides general trends for aircraft with a VPF as the main thrust reversal unit. Generally, debris ingestion increases with lower aircraft speed and debris material density. The benefits of having a VPF are highlighted since it acts as an additional “protective layer” to the engine core and stops and redirects incoming debris from the nominal intake. The assessment of ingestion of foreign objects in realistic end-of-landing-run conditions as described in this study is important to examine the feasibility of reverse thrust-capable VPF engines for future sustainable aircraft.
Copyright © 2026 by Rolls-Royce plc.
Keywords: 40 Engineering; Energy; 4001 Aerospace engineering; 4004 Chemical engineering